2020
DOI: 10.1016/j.marenvres.2020.105176
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting responses to salinity and future ocean acidification in arctic populations of the amphipod Gammarus setosus

Abstract: Hawliau Cyffredinol / General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research.• You may not further distribute the material or use it for any profit-maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…This strong influence of salinity on amphipod performance is also illustrated by the results of Egilsdottir et al ( 2009 ) who found out that lowering the salt content, more than lowering pH, has a negative impact on embryonic development in a (temperate) intertidal amphipod species. Similarly, Brown et al ( 2020 ) found lower salinity to reduce energy budgets (and thus in the longer term growth and reproduction) in an Arctic amphipod species.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This strong influence of salinity on amphipod performance is also illustrated by the results of Egilsdottir et al ( 2009 ) who found out that lowering the salt content, more than lowering pH, has a negative impact on embryonic development in a (temperate) intertidal amphipod species. Similarly, Brown et al ( 2020 ) found lower salinity to reduce energy budgets (and thus in the longer term growth and reproduction) in an Arctic amphipod species.…”
Section: Discussionmentioning
confidence: 81%
“…There are several studies that investigated effects of decreasing pH on marine amphipods (Benítez et al, 2016 ; Brown et al, 2020 ; Egilsdottir et al, 2009 ; Goulding et al, 2017 ; Hauton et al, 2009 ; Passarelli et al, 2017 ; Schram et al, 2016 ), but some species appear to be more resilient than others (Passarelli et al, 2017 ). Crustaceans may not be as much affected by ocean acidification as mollusks or echinoderms, because their exoskeletal CaCO 3 is mostly in the more stable form of calcite rather than the more soluble aragonite form (Whiteley, 2011 and citations therein).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, C. glacialis nauplii have shown upregulation of Na + /H + -antiporters independent of ATPase as a response to OA 16 , which one could hypothesise also may be the case in the copepodites. Arctic populations of the amphipod Gammarus setosus also do not experience increased ATPase activity during OA conditions 46 . It seems that C. glacialis faces OA without any ATP dependent acid/base regulation activity.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term exposure to salinity stimulation can result in disorders in immune and antioxidant capacity of organisms. [ 19 ]. Numerous reports have been published on the impact of salinity on the immune defense and physiological and biochemical indices in crustaceans.…”
Section: Introductionmentioning
confidence: 99%